Recovery of Functional Proteins from Pig Brain Using pH-Shift Processes - Jaruwan Chanted; Worawan Panpipat; Ling-Zhi Cheong; Manat Chaijan (Foods, 2022)
The goal of this work is to explore if pH-shift processing could be used as a cold refinery technique to manufacture pig brain protein isolate (PI). Pig brain protein had the highest solubility at pH 2 (acid method) and pH 12 (alkaline method). As the protein solution’s zeta-potential was near 0 with the lowest solubility, pH 5.0 was chosen as the precipitation pH. Alkaline process produced a 32% dry matter yield with phospholipid content of 35 mg/100 g. The alkaline-made PI was better at forming soft gels and had good emulsifying and foaming capabilities. Although the acid-made PI included less residual lipid and total haem protein and was whiter in colour, it could not be gelled. Acid-made PI was more prone to lipid oxidation with a poorer ability to function as an emulsifier and foaming agent. Thus, functional proteins from pig brain may be isolated using the alkaline pH-shift technique.